In-belt vibration monitoring of conveyor idlers and using wavelet package decomposition and artificial intelligence for early fault detection - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2018)
Dissertation (MEng)--University of Pretoria, 2018.